Polycyclic Aromatic Hydrocarbon (PAH) Contents of Four Species of Smoked Fish from Different Sites in Senegal - El Hadji Moussa Diop; Bou Ndiaye; Alioune Sow; Falilou Mbacké Sambe; Mamadou Sall; Mamadou Saliou Thiam (International Journal of Analytical Chemistry)
Polycyclic aromatic hydrocarbons (PAHs) are compounds resulting from any incomplete combustion process. These are pollutants that have proven toxicity due to their carcinogenic nature and can contaminate food during traditional smoking methods. Their highly toxic effect on human health requires monitoring of their levels in food products and the development of appropriate analytical methods for their determination. Thus, this study was conducted to assess the level of PAHs contamination of four (4) species of smoked fish (Arius heudelotii, Sardinella aurita, Ethmalosa fimbriata, and Sardinella maderensis) which were sampled in seventeen (17) localities in Senegal. The compounds targeted in this study were benzo(a)pyrene (B(a)P), benzo(a)anthracene (B(a)A), benzo(b)fluoranthene (B(b)F), and chrysene (Chr). The QuEChERS method was used for the extraction of PAHs, and their contents were quantified by gas chromatography (GC) coupled with mass spectroscopy (MS). The validation method was performed in accordance with the French standard NF V03-110 (2010). Satisfactory linearity (R2 > 0.999), LOD (0.05–0.09 μg/kg), LOQ (0.19–0.24 μg/kg), and precision (1.33–3.13%) of the four PAHs were obtained. The results of analysis in the 17 localities showed that all samples are contaminated by the four (4) PAHs with great variability of the contents between the different species and their origin. The B(a)P and ∑4PAHS contents in the samples ranged from 1.7 to 33 µg/kg and from 4.8 to 1082.3 µg/kg, respectively. Twelve (12) samples showed high levels of B(a)P, ranging from 2.2 to 33 µg/kg, thus exceeding the maximum authorized level (2 µg/kg). Fourteen (14) samples showed an overall ∑4PAHS content varying from 14.8 to 1082.3 µg/kg, which is above the maximum authorized limit (12 µg/kg). The principal component analysis showed that sardinella (Sardinella aurita and Sardinella maderensis) have very low levels of B(a)P, B(b)F, B(a)A, and Chr contents. However, high ∑4PAHS contents characterize smoked fish of the Kong species (Arius heudelotii), from Cap Skiring, Diogne, Boudody, and Diaobé, and of the Cobo species (Ethmalosa fimbriata) from Djiffer. Thus, based on the authorized limits for PAHs in smoked fish, it appears that smoked fish of the sardinella species are less carcinogenic for human consumption.